Borderline Personality Traits in Patients With Epilepsy - Sara Shoja; Nikoo Saeedi; Seyed Mehran Homam (Caspian Journal of Neurological Sciences, 2023)
Background: Although much research on patients with epilepsy (PWE) has focused on psychiatric disorders such as depression, anxiety, and psychotic disorders, the relationship between epilepsy and personality disorders has not been frequently studied. Objectives: The study aimed to evaluate borderline personality traits in PWE. Materials & Methods: In this case-control study, we evaluated 211 PWE who were consecutively referred to 22 Bahman Hospital, Mashhad, Iran, in 2021. We also compared the patients with an age-matched and gender-matched control group. The Borderline personality traits were assessed by the second subscale of the schizotypal questionnaire (STB) which is known as the borderline personality scale questionnaire. Data were coded and analyzed by SPSS software, version 20. Results: Epilepsy group had significantly higher borderline personality features in comparison with the control group (P=0.029). PWE had significantly higher scores in hopelessness (P=0.017) and impulsivity factors (P=0.046) on the STB questionnaire. Our results revealed that PWE who were married (P=0.011) and who had epilepsy for more than 10 years, had significantly higher borderline personality traits (P=0.04). Conclusion: PWE are more likely to have borderline personality traits. Therefore, it is important to screen epileptic patients to detect it earlier to avoid further consequences and its possible effects on therapeutic responses.